Diabetes type 1 and pregnancy outcome at University Hospital Center Split : a retrospective study = Trudnoća i porođaj uz dijabetes melitus ovisan o inzulinu u KBC-u Split : retrospektivno istraživanje - Praprotnik, Doris (Array, 2021)
Aim: To evaluate the prevalence, assessment, and perinatal outcome of pregnancies complicated with diabetes mellitus type 1 (DM type 1) at a tertiary perinatal center in the town of Split, Dalmatia County. Materials and methods: The investigation was designed as a retrospective cohort study. All pregnant women with DM type 1 that were supervised and gave birth at Clinical Department of Obstetrics and Gynecology, Split University Hospital Center during a 7-year period (2009-2015), including those diagnosed in 2015 and having delivered in 2016, were included in the study group. Data were collected by the census method from legal protocol books. Control group included DM type 1-free pregnancies entered in the same protocol books just following a particular study woman, if meeting all inclusion and exclusion criteria. Results: There were 70 DM type 1 pregnancies, accounting for 0.2% of all deliveries. DM type 1 group newborns were statistically heavier (3650±605 vs. 3428±591g; p=0.031), more frequent large for gestational age (24.3% vs. 5.7%; p=0.002) and macrosomic (24.3% vs. 10%; p=0.033). Compared to control group, DM type 1 women had a significantly higher delivery rate in the 37th to 39th week of gestation (84.3% vs. 58.6%; p=0.001) and higher cesarean section rate (61.4% vs. 32.9%; p=0.001). Conclusion: DM type 1 significantly influences perinatal outcome. It requires multidisciplinary approach and complete supervision should be provided at specialized centers. Respecting the fetal origin of adult diseases theory, inappropriate protocol(s) and/or individual decision(s) can have many health consequences throughout newborns life, which highlights DM type 1 pregnancies to a public health level issue.